2014
DOI: 10.1103/physrevd.90.075013
|View full text |Cite
|
Sign up to set email alerts
|

Light neutralino dark matter inU(1)models

Abstract: We analyze the prospects for light neutralino dark matter in the minimal supersymmetric model extended by a U (1) gauge group. We allow the neutralino to be an arbitrary admixture of singlet and doublet higgsinos, as well as of the three gauginos, and we require agreement with the data from the direct and indirect dark matter detection experiments, while maintaining consistency of the model with the relic density, and with the recent Higgs data from the LHC. The constraints have implications for the structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Detailed studies have already been carried out for this particular channel. For example, h → γγ is studied in a wide variety of supersymmetric (SUSY) models namely, the minimal supersymmetric standard model (MSSM) , its next-to-minimal version (NMSSM) [27][28][29][30][31][32][33][34][35], the constrained MSSM (CMSSM) [36][37][38][39][40][41] and also in (B-L)SSM [42][43][44][45], µνSSM [46], left-right supersymmetric models [47], and in U(1) ′ extension of MSSM [48]. In [49], a triplet-singlet extension of MSSM has been studied and µ γγ is computed.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…Detailed studies have already been carried out for this particular channel. For example, h → γγ is studied in a wide variety of supersymmetric (SUSY) models namely, the minimal supersymmetric standard model (MSSM) , its next-to-minimal version (NMSSM) [27][28][29][30][31][32][33][34][35], the constrained MSSM (CMSSM) [36][37][38][39][40][41] and also in (B-L)SSM [42][43][44][45], µνSSM [46], left-right supersymmetric models [47], and in U(1) ′ extension of MSSM [48]. In [49], a triplet-singlet extension of MSSM has been studied and µ γγ is computed.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…In this section, we describe the simplified dark matter model we use in our analysis. Majorana fermions recently emerged as the most plausible dark matter particle candidates in the simplified model context [80,[122][123][124][127][128][129][130][131]. Motivated by this, we assume that dark matter consists of a single Majorana fermion, which we denote by χ. Additionally, motivated by the listed literature and the Higgs portal, we assume that the interaction between the dark matter particle and standard fermions is mediated by a scalar particle S [132,133].…”
Section: The Dark Matter Modelmentioning
confidence: 99%
“…In the recent literature it was shown that Majorana fermions are one of the most plausible dark matter candidates [42][43][44][45][46][47][48][49].…”
Section: Jhep05(2016)033mentioning
confidence: 99%